Thermosensitive polymeric micelles based on the triblock copolymer poly(d, l‐lactide)‐b‐poly(N‐isopropyl acrylamide)‐b‐poly(d, l‐lactide) for controllable drug delivery. Issue 37 (29th May 2017) - Li, Peng; Zhang, Zhenfang; Su, Zhiqiang; Wei, Gang
ABSTRACT: A thermosensitive amphiphilic triblock copolymer, poly(d, l ‐lactide) (PLA)‐ b ‐poly( N ‐isopropyl acrylamide) (PNIPAAM)‐ b ‐PLA, was synthesized by the ring‐opening polymerization ofd, l ‐lactide; the reaction was initiated from a dihydroxy‐terminated poly( N ‐isopropyl acrylamide) homopolymer (HO‐PNIPAAM‐OH) created by radical polymerization. The molecular structure, thermosensitive characteristics, and micellization behavior of the obtained triblock copolymer were characterized with Fourier transform infrared spectroscopy, 1 H‐NMR, gel permeation chromatography, dynamic light scattering, and transmission electron microscopy. The obtained results indicate that the composition of PLA‐ b ‐PNIPAAM‐ b ‐PLA was in good agreement with what was preconceived. This copolymer could self‐assemble into spherical core–shell micelles (ca. 75–80 nm) in aqueous solution and exhibited a phase‐transition temperature around 26 °C. Furthermore, the drug‐delivery properties of the PLA‐ b ‐PNIPAAM‐ b ‐PLA micelles were investigated. The drug‐release test indicated that the synthesized PLA‐ b ‐PNIPAAM‐ b ‐PLA micelles could be used as nanocarriers of the anticancer drug adriamycin (ADR) to effectively control the release of the drug. The drug‐delivery properties of PLA‐ b ‐PNIPAAM‐ b ‐PLA showed obvious thermosensitive characteristics, and the release time of ADR could be extended to 50 h. This represents a significant improvement from previous PNIPAAM‐based drug‐delivery systems. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45304. Abstract :